If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -2y = 2 Combine like terms: 4y + -2y = 2y 2y = 2 Solving 2y = 2 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '2'. y = 1 Simplifying y = 1
| 8(x+4)+2(x+4)=7x-7 | | -3x+6+x=6 | | (x+1)*(x+3)*(x+5)*(x+7)+15=0 | | 15x^2+4y+2x-8+6xy=0 | | 2(2d-8)=96+(d+3) | | x-7=8x+14 | | log(9)*3-x=log(9)*5x-15 | | -8x+1=-80 | | 2s+4h+6u+8t=100 | | 2s+3h+5u+6t=100 | | X-.2X=81 | | -8+4x=-28 | | 21-5x=13-7x | | 52+x-28=55 | | x^2-24x=44 | | log(4)4x-20=5 | | 2+2=.5x-1 | | 75+x-60=40 | | 2+2=2x-1 | | 2+2=22x-1 | | 64+x-39=47 | | 28+x-20=42 | | 1.25-22= | | 9+10=x+1 | | 45+x-5=80 | | 9h-27=63 | | T=7M+3 | | x^2(x-3)-2x(x-3)+(x-3)=0 | | 100x+y=x+50y | | 100x+y=x+2y | | 10x+y=x+2y | | 347*25=8675 |